Effectiveness of Ultrasound Imaging in Assessing the Palpation Skills of Rotating Physicians - Huang, Peizhen; Zheng, Bin; Liu, Shan; Xu, Lin; Chen, Chengchun; Zhan, Shubei (Frontiers in Genetics, 2022)
As an important means of physical examination, palpation is usually limited to the physical examination before surgery and used as an auxiliary method for disease diagnosis in the field of surgery. In practice, palpation is also used in every aspect of the surgical procedure, and its application is of great significance to surgery, and the purpose of this study is to study the use of ultrasound imaging to evaluate the positioning of muscles by palpation by rotating physicians The capacity of bone structure. In practice, palpation is also used in every aspect of the surgical procedure, and its application is of great significance to surgery, and the purpose of this study was to investigate the ability of ultrasound imaging to assess the ability of rotational physicians to locate musculoskeletal structures by palpation. Rotation physicians were asked to palpate and locate the long head tendon of the biceps (LHB), posterior tibialis (TPT), acromioclavicular joint (ACJ) and medial tibiofemoral joint (TFJ) spaces on two volunteer models, After positioning, a truncated steel needle was attached to the skin and parallel to the palpable structure, and the position of the steel needle relative to the designated structure was assessed by ultrasound imaging, using the Cohen kappa test to study the inter-rater agreement. The results showed that the assessor's Kappa coefficient for judging the location of all structures was 0.816, LHB was 1.00, TPT was 0.912, ACJ space was 0.796, TFJ medial space was 0.844, and the success rate of palpation: TPT was 62.2%, TFJ medial space was 37.8% , ACJ clearance was 24.3%, LHB was 8.1%. In conclusion, the teaching methods of anatomy and palpation skills need further improvement, and ultrasound imaging is an effective tool for assessing palpation skills.